Chiral symmetry breaking and the Josephson current in a ballistic superconductor-quantum wire-superconductor junction
We evaluate the Josephson current through a quasi-1D quantum wire coupled to bulk superconductors. It is shown that the interplay of Rashba spin–orbit interaction and Zeeman splitting results in the appearence of a Josephson current even in the absence of any phase difference between the superconductors. In a transparent junction (D ≃ 1) at low temperatures this anomalous supercurrent Jan appears abruptly for a Zeeman splitting of the order of the Andreev level spacing as the magnetic field is varied. In a low transparency (D